Analisis Dividend Payout Ratio pada PT. Unilever indonesia Tbk. - Rita Patonah (Universitas Indraprasta PGRI, 2021)
The purpose of this research is to find out: 1) The development of net income at PT Unilever Indonesia Tbk; 2) Dividend policy applied to PT Unilever Indonesia Tbk; 3) Effect of net income on dividend policy on PT Unilever Indonesia Tbk. This study uses descriptive research methods with quantitative approaches. The data analysis techniques used are cholera analysis, determination coefficient analysis, and t-test. The results showed that: 1) Net income at PT. Unilever Indonesia, Tbk every year has increased; 2) Dividend Payout Ratio (DPR) in PT. Unilever Indonesia, Tbk experienced fluctuations tending to fall; 3) Net income negatively affects the dividend policy at PT. Unilever Indonesia, Tbk.